2019
DOI: 10.1017/s136898001900140x
|View full text |Cite
|
Sign up to set email alerts
|

Reducing childhood malnutrition in Bangladesh: the importance of addressing socio-economic inequalities

Abstract: Objective:To obtain projections of the prevalence of childhood malnutrition indicators up to 2030 and to analyse the changes of wealth-based inequality in malnutrition indicators and the degree of contribution of socio-economic determinants to the inequities in malnutrition indicators in Bangladesh. Additionally, to identify the risk factors of childhood malnutrition.Design:Cross-sectional study. A Bayesian linear regression model was used to estimate trends and projections of malnutrition. For equity analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 35 publications
7
47
1
Order By: Relevance
“…Surprisingly, watching television less than once a week increased the risk of coexistence of stunting, wasting and underweight by 54% among children than households not exposed to this media. This nding was not consistent with a study conducted in Bangladesh [8,33]. Inconsistent contents of food advertisements regarding dietary recommendations and poorer understanding of nutrition from food advertisements in television might cause adverse nutritional outcomes, indicating need of attention of the policy makers to the matter [34,35].…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Surprisingly, watching television less than once a week increased the risk of coexistence of stunting, wasting and underweight by 54% among children than households not exposed to this media. This nding was not consistent with a study conducted in Bangladesh [8,33]. Inconsistent contents of food advertisements regarding dietary recommendations and poorer understanding of nutrition from food advertisements in television might cause adverse nutritional outcomes, indicating need of attention of the policy makers to the matter [34,35].…”
Section: Discussioncontrasting
confidence: 76%
“…In recent survey, we found the risk of coexistence of stunting, wasting and underweight increased by 402% in children of uneducated mothers which was insigni cant in 2014 survey. Lack of maternal education was not assessed most in uential risk factors of child malnutrition in previous studies in Bangladesh and other developing countries [8,23,24,25]. Current evidence also showed that three out of fty children of uneducated mothers were suffering from coexistence of stunting, wasting and underweight as children of underweighted mothers did.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Maternal exposure to physical violence substantially increased a child's risk of stunting in our study. At the household level, evidence suggests that children in households in the poorest socio-economic groups have higher prevalence of malnutrition [71][72][73]. This emphasizes the impact of the differential availability of resources to families that act as a major determinant of malnutrition.…”
Section: Discussionmentioning
confidence: 99%